Assessment of import substitution indicators in Russia - I. A. Aksenov (Вестник университета)
Import dependence is the oldest problem that has been faced by various states. Back in the Middle Ages, Russia faced the issues of deficit of products and certain technologies, which were compensated by import. Starting from 2014, it became obvious that certain sectors of the economy are highly dependent on imported technologies and a number of foreign goods, which formed trends for the import substitution policy development. Despite domestic technological solutions implementation, their qualitative characteristics do not allow to ensure the required level of competitiveness in the global market. The purpose of the study is to assess the current indicators of import substitution in Russia. When solving the tasks set in the research paper, the author used general scientific and special research methods such as system approach (to determine the import substitution directions), analysis and synthesis (to study the import substitution indicators), deduction and induction (to analyze the issues), and statistical analysis (to analyze statistical indicators on the import substitution policy implementation) methods. The key indicators of import substitution in Russia have been analyzed. It has been concluded that the main priority of the domestic import substitution policy is to reduce the share of imports in the structure of goods supply and to develop the country’s export potential.